Self-Censorship Regulatory Structure: Can We Control Political of Hates, Violence & Sex in Children Computer & Video Games? - Hasmah Zanuddin (The Indonesian Journal of Communication Studies, 2008)
This article examines some of the extreme negative content available to teenagers and young children in the market. Extreme negative values such as political of hates, violence and sex in some of the children computer and video games were made possible due to several factors such as lacking in regulatory structure, week policy implementation, rampant of illegal and uncensored materials. Computer and video games have been the subject of frequent controversy and censorship, due to the depiction of graphic violence, sexual themes, racism, advertising, eavesdropping, consumption of illegal drugs, consumption of alcohol or tobacco, propaganda or profanity in some games. Among others, critics of video games sometimes include parents’ groups, politicians, organized religion groups, and other special interest groups. Young children who see violent acts in movies, shows, and games may not be able to tell the difference between “make-believe” and real life. They may not understand that real violence hurts and kills people. When the “good guys” or heroes use violence, children may learn that it is okay to use force to solve problems. Younger children may even become more afraid of the world around them. Can self-censorship and ratings system help?